Phenolic Acids, Phenolic Aldehydes and Furanic Derivatives in Oak Chips: American vs. French Oaks - Cabrita, M.J.; Barrocas Dias, C.; Costa Freitas, A.M. (South African Journal of Enology and Viticulture, 2011)
Phenolic acids (gallic, vanillic, syringic and ellagic acids), phenolic aldehydes (vanillin, syringaldehyde, coniferaldehyde and sinapaldehyde) and furanic derivatives (furfural, 5-methylfurfural and 5-hydroxymethylfurfural) were quantified in commercial American and French oak chips. Chips with different sizes and toast degrees were used. Compounds were extracted directly from the wood samples in order to determine possible differences among woods as well as toast degree. Likewise, the compounds were extracted from a synthetic wine solution to which the chip woods had been added. The results show that French wood chips are generally richer than the American ones. The total amount of phenolic compounds increases with toasting level, with the non-toasted chips being the poorest ones. The degree of extraction from the synthetic wine solution seems to be related to the shape of the chips, rather than to the wood type or toast degree.